Effectiveness and safety of vedolizumab in a matched cohort of elderly and nonelderly patients with inflammatory bowel disease: the IG‐IBD LIVE study. Issue 1 (12th May 2022) - Pugliese, Daniela; Privitera, Giuseppe; Crispino, Federica; Mezzina, Nicolò; Castiglione, Fabiana; Fiorino, Gionata; Laterza, Lucrezia; Viola, Anna; Bertani, Lorenzo; Caprioli, Flavio; Cappello, Maria; Barberio, Brigida; et al.
Summary: Background: Vedolizumab registration trials were the first to include elderly patients with moderate‐to‐severe ulcerative colitis (UC) or Crohn's disease (CD), but few real‐life data have been reported in this population. Aims: We investigated the effectiveness and safety of vedolizumab in matched cohorts of elderly and nonelderly UC and CD patients. Methods: The Long‐term Italian Vedolizumab Effectiveness (LIVE) study is a retrospective‐prospective study including UC and CD patients who started vedolizumab from April 2016 to June 2017. Elderly patients (≥65 years) were matched clinically 1:2 to nonelderly patients (18–64 years); the 2 groups were followed until drug discontinuation or June 2019. Results: The study included 198 elderly (108 UC, 90 CD) and 396 matched nonelderly patients (205 UC, 191 CD). Nonelderly UC patients had a significantly higher persistence on vedolizumab compared to elderly patients (67.6% vs. 51.4%, p  = 0.02). No significant difference in effectiveness was observed between elderly and nonelderly CD patients (59.4% vs. 52.4%, p  = 0.32). Age ≥65 years was associated with lower persistence in UC; for CD, previous exposure to anti‐TNF‐α agents, Charlson comorbidity index >2 and moderate‐to‐severe clinical activity at baseline were associated with lower persistence. There were recorded 130 adverse events, with comparable rates between the two groups. A Charlson comorbidity index >2 was associated with an increased risk of adverse events. Conclusion: Vedolizumab can be considered a safe option in elderly IBD patients. Its effectiveness in elderly UC patients may be reduced, while no age‐dependent effect on effectiveness was observed in CD. Abstract :